A CONCEPTUAL CLEANCARE DIGITAL PLATFORM BUSINESS MODEL: ENHANCING THE WELL-BEING AND NURTURING LOW-INCOME B40 COMMUNITIES AS CLEANCARE-PRENEURS IN THE GOMBAK COMMUNITY - MEGAT MOHD SUHAIMI, PUTERI NOOR FARHANA; RAMLAN, PUTERI SABRINA RAYSA; AHMAD YUSOF, NUR SYAHIRAH; MUHAMMAD SHAKIR, NAAFILAH HUDAA; AHMAD DAHLAN , ABDUL RAHMAN (Journal of Information Systems and Digital Technologies, 2024)
This paper is to offer a conceptual platform business model of laundry and cleaning services, called CleanCare, embedded with a digital platform/app. The value proposition of CleanCare is to help improving the quality of life that meets the expectation and needs of the Gombak community by providing a comprehensive digital platform laundry and sertu cleaning business model. The business model provides services like efficient pickup, sertu and careful washing method, professional folding and delivery service to the front of customers’ homes; aligned with the United Nations’ Sustainable Development Goals; SDG 3 - Good Health and Well-being, SDG 8 - Decent Work and Economic Growth, and SDG 9 - Industry, Innovation and Infrastructure. In addition to save the houseowners time and effort, this service maintains the highest standards of hygiene and cleanliness by streamlining the laundry process that align with SDG 3 for reducing the Gombak communities from the risk of being infected to dangerous bacteria and germs from dirty clothes. The paper adapts the design thinking methodology, which includes empathizing, defining, ideating, prototyping, and testing processes. CleanCare business model is designed, tested, and established as a multi-sided platform business by first understanding the job-to-do, essential gains, and extreme pains faced by the various customer segments (CS) – cleaning service seekers, cleaning service providers, B40-preneurs and donors. In formulating business model options as a possible solution that is relevant to the various CS, business modelling tools like the Value Proposition Design Canvas (VPC), Business Model Canvas (BMC), and Business Environmental Map (EM) are used in the ideation, designing, and testing of the initial/prototype business model, and finally establishing the CleanCare business model. Hence, this paper offers the CleanCare business model aims to pave the way towards the betterment of Gombak community quality of life by leveraging on trusted digital platforms for laundry and sertu cleaning services.